2018
DOI: 10.1136/bmjopen-2017-021103
|View full text |Cite
|
Sign up to set email alerts
|

Association of total homocysteine with blood pressure in a general population of Chinese adults: a cross-sectional study in Jiangsu province, China

Abstract: ObjectivesWe aimed to evaluate the relation of total homocysteine (tHcy) concentrations with systolic blood pressure (SBP) and diastolic blood pressure (DBP) levels, and examine the possible modifiers in the association among a general population of Chinese adults.DesignA cross-sectional study.SettingThe study was conducted within 21 communities in Lianyungang of Jiangsu province, China.ParticipantsA total of 26 648 participants aged ≥35 years and with no antihypertensive drug use were included in the final an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
3
14
2
3
Order By: Relevance
“…Mechanisms by which hesperidin could contribute to the control of BP and PP are associated with improvements on endothelial function, oxidative stress, and inflammation [8]. Homocysteine is associated with these risk factors and with a renin-angiotensin system activation to induce a BP increase [43]. In agreement with this, we observe a decrease in homocysteine concomitant with decreases in BP and PP after hesperidin treatments.…”
Section: Discussionsupporting
confidence: 81%
“…Mechanisms by which hesperidin could contribute to the control of BP and PP are associated with improvements on endothelial function, oxidative stress, and inflammation [8]. Homocysteine is associated with these risk factors and with a renin-angiotensin system activation to induce a BP increase [43]. In agreement with this, we observe a decrease in homocysteine concomitant with decreases in BP and PP after hesperidin treatments.…”
Section: Discussionsupporting
confidence: 81%
“…Homocysteine (Hcy) has been involved in the pathogenesis of hypertension by producing endothelial injury [3,4], increasing oxidative stress [5], stimulating the proliferation of vascular smooth muscle cells (VSMCs) [6], and altering the elastic properties of the vascular wall [7]. Elevated Hcy and its related genetic variants have been associated with blood pressure [8][9][10][11][12], hypertension [13][14][15], and related vascular complications, e.g., atherosclerosis [16,17], coronary heart disease [18,19], and stroke [20,21], in humans. In the process of Hcy-induced hypertension, the endothelial injury resulting from Hcy promotes platelet consumption and adherence which stimulates the proliferation of VSMCs through releasing mitogenic factors [22], thereby contributing to atherosclerosis, arterial stiffness, and high blood pressure [23,24] Furthermore, platelet activation has been associated with Hcy [25] but also hypertension [26] in population studies.…”
Section: Introductionmentioning
confidence: 99%
“…The study identified a gender difference, indicating that Hcy was not a significant risk factor for women. A study in Liao‐Ning, Jiang‐Su, and Xin‐Jiang provinces found significant and positive associations of homocysteine concentrations with hypertension and BP …”
Section: Discussionmentioning
confidence: 97%
“…The design of the studies contributed to the different observed results. In most retrospective studies, such as case‐control studies and cross‐sectional studies, plasma Hcy levels were related to an increase in BP and hypertension . However, different conclusions were reached in large prospective studies after adjusting for confounding factors.…”
Section: Discussionmentioning
confidence: 99%